Mortalidade infantil em município sede de Regional de Saúde : tendência e fatores associados - Silva, Anna Lúcia da (2013)
Infant mortality, defined as deaths in children under one year of age, is an indicator of quality of life and health services offered to the population. The infant mortality rates have declined in recent decades, but one can not fail to monitor them annually, in addition to studying the factors associated with infant deaths to plan actions to the real problems of the locality. The aim of this study was to analyze trends in infant mortality and associated factors in Paranavai, PR. Ecological study of time series whose data source was the Information System on Live Births (SINASC), Information System (SIM) and the Brazilian Institute of Geography and Statistics (IBGE). To study the trend of infant mortality and its components used data from 1990 to 2011 divided into two periods , 1990-1999 and 2000-2011, and to study the factors associated with the data from 2000 to 2011 divided into three-year periods of so that the univariate analysis and logistic regression were made in the first and last three years. In trend analysis we used the method of polynomial regression, SPSS version 20.0, significance level of 5 %, considering that the best model with greater statistical significance. To study the association between the independent variables and mortality were used chi -square association test, and Fisher's exact test when indicated, considering the level of significance of 5 %. The strength of the association was assessed using estimates adjusted Odds Ratio. Results showed that from 1990 to 1999 there was a decreasing trend for infant mortality and its components early neonatal and post - neonatal, and stability for the neonatal late. For the period 2000 to 2011houve growing trend for infant mortality rates and late neonatal, and decreasing trend for the post-neonatal period. The early neonatal component remained stable. Factors independently associated with infant death were the same for the two periods, low birth weight (OR 17,76; 31,44), length of gestation less than 36 weeks (OR 12,32; 11,08), maternal education less than eight years (OR 2,73; 2,98), Apgar score at 1 minute (OR 8,88; 6,87), Apgar score at 5 minutes (OR 18,98; 25,67) and number of prenatal visits natal below seven (OR 1,86; 2,45). The results suggest that the health care of the resident population in Paranavaí is not occurring in a satisfactory manner, requiring closer monitoring in relation to the provision of assistance to pregnant women and newborns and chang.